2010
DOI: 10.1063/1.3501967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of top electrode materials on bipolar resistive switching behavior of gallium oxide films

Abstract: Well-developed bipolar resistive switching behaviors have been revealed in Pt/GaOx/ITO stacks without an electroforming process. By substituting platinum with titanium as the top electrode, switching polarity changed from “counter-Figure-8” to “Figure-8.” The modulation of Schottky barrier at the Pt/GaOx interface induced by migration of oxygen vacancies was proposed to explain the switching in Pt/GaOx/ITO stacks, while the switching in Ti/GaOx/ITO stacks was ascribed to the redox reaction at the Ti/GaOx inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…This oxide is-due to its high gallium excess-a heavily self-doped, n-type semiconductor 29 . Recently, several authors reported that a-GaO x thin films with Pt as TE and ITO or TiN as bottom electrode (BE) reveal a counter figure-eight hysteretic loop in their I-V characteristics 30,31 . They proposed a filamentary switching mechanism, similar to that introduced for TiO x , to explain GaO x switching [30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…This oxide is-due to its high gallium excess-a heavily self-doped, n-type semiconductor 29 . Recently, several authors reported that a-GaO x thin films with Pt as TE and ITO or TiN as bottom electrode (BE) reveal a counter figure-eight hysteretic loop in their I-V characteristics 30,31 . They proposed a filamentary switching mechanism, similar to that introduced for TiO x , to explain GaO x switching [30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] In recent years, reversible bipolar resistance switching behaviors in gallium oxide thin films were obtained and investigated. [10][11][12][13][14] For instance, Gao et al investigated the effect of top electrode materials on bipolar resistive switching behavior of gallium oxide films and pointed out that the migration of oxygen vacancies in the vicinity of the electrode area plays an important role in the resistive switching process. 10 Aoki et al directly observed reversible enrichment and depletion of oxygen ions at the blocking electrodes responding to the bias polarity, and proved that oxygen ion mobility causes bipolar memristive behavior in gallium oxide films.…”
mentioning
confidence: 99%
“…On the basis of the above analysis, the formation and rupture of oxygen vacancies related filament could explain the physical mechanism of the resistive switching effect in Pt/IOC/TiN memory devices [30,31]. Fig.…”
Section: Resultsmentioning
confidence: 98%